2017
DOI: 10.1515/botlit-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

New woody alien plant species recorded in Lithuania

Abstract: Gudžinskas Z., Petrulaitis L., Žalneravičius E., 2017: New woody alien plant species recorded in Lithuania. -Bot. Lith., 23(2): 153-168.Many woody plant species that originate from various regions of the world have been introduced in other regions or continents and are used in ornamental gardening, silviculture, erosion control, for fruit sources or other purposes. Woody plants selected for introduction usually originate from regions with similar climate conditions; therefore, after certain time lag they start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Our study, though based on only 12 sampled mature individuals, revealed that only monoecious individuals were present in the four studied populations in Lithuania. The fact that in all studied populations we found monoecious individuals explains the presence of a certain amount of ripe fruits (Gudžinskas et al 2017). Interestingly, in 2019 we recorded an individual of C. orbiculatus in Ķemeri (Latvia) with solitary fruits and we suppose that this plant is also monoecious with prevailing functionally male flowers.…”
Section: Flower Gendermentioning
confidence: 53%
See 3 more Smart Citations
“…Our study, though based on only 12 sampled mature individuals, revealed that only monoecious individuals were present in the four studied populations in Lithuania. The fact that in all studied populations we found monoecious individuals explains the presence of a certain amount of ripe fruits (Gudžinskas et al 2017). Interestingly, in 2019 we recorded an individual of C. orbiculatus in Ķemeri (Latvia) with solitary fruits and we suppose that this plant is also monoecious with prevailing functionally male flowers.…”
Section: Flower Gendermentioning
confidence: 53%
“…Information on the distribution of C. orbiculatus in Europe was quite dispersed over numerous publications and other sources of information. According to these sources C. orbiculatus has been recorded in 13 European countries: Austria (Leonhartsberger 2013; Sauberer and Till 2015), Belgium (Verloove 2006(Verloove , 2013, the Czech Republic (Červinka and Sádlo 2000;Pyšek et al 2012;Pergl et al 2016), Germany (Brandes 2011;Adolphi et al 2012;Adolphi 2015;Alberternst 2018;Alberternst and Nawrath 2018), Latvia, Lithuania (Gudžinskas et al 2017), the Netherlands (Beringen et al 2017), Norway (Gederaas et al 2012;Beringen et al 2017), Poland (Purcel 2010(Purcel , 2011, the European part of Russia (Morozova 2014, without exact locality), Sweden (Beringen et al 2017), Ukraine and United Kingdom (Stace 1997;Beringen et al 2017;BSBI 2018). In total, 58 sites of occurrence of this species have been reported so far and they fall into 42 grid cells of the "Atlas Florae Europaeae" (Figure 3).…”
Section: Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…More than thirty years have passed since the start of my studies in 1987 on alien plant species in Lithuania. During this time, more than 200 species of earlier non-registered alien plants have been discovered, and a lot of information on their distribution, naturalization, ecology and biology has been collected (Gudžinskas, 1989(Gudžinskas, , 1993(Gudžinskas, , 1994(Gudžinskas, , 1997a(Gudžinskas, , 2017Gudžinskas et al, , 2017. Some plant species have not been identified immediately, and only after several decades, with additional information gathered, it has become possible to determine their identity, although a small fraction of the samples collected so far have not been identified and this should be done in the future.…”
Section: Introductionmentioning
confidence: 99%